2016
DOI: 10.1128/aac.01256-16
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Surveillance of Novel Oxazolidinone Resistance Gene optrA in Enterococcus Isolates in China from 2004 to 2014

Abstract: A total of 2,201 nonduplicate enterococcal isolates collected from 29 hospitals in 23 cities in China between 2004 and 2014 were screened for the oxazolidinone resistance gene optrA; 45 isolates (2.0%) were optrA positive with 11 OptrA variants identified. The positive rate of optrA increased from 0.4% to 3.9% during the 10-year surveillance period. Pulsed-field gel electrophoresis (PFGE) and multilocus sequence type (MLST) analysis revealed that 37 optrA-positive Enterococcus faecalis isolates clustered into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 14 publications
2
46
2
3
Order By: Relevance
“…Linezolid resistance rates remain generally low in enterococci causing infections worldwide (<1 %) [1,3], however, acquired linezolid resistance genes (cfr, optrA and/or poxtA) are being increasingly reported in different enterococcal species and across different settings [2][3][4][5][6][7]. Among the three transferable linezolid resistance genes, optrA has been the main one responsible for the recent increase in linezolid-resistant enterococci (LRE) in human isolates [8][9][10][11][12][13]. According to available studies, optrA-carrying LRE are globally circulating in hospitals since at least 2005 [14], while the first description in food-producing animals dates from 2008 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Linezolid resistance rates remain generally low in enterococci causing infections worldwide (<1 %) [1,3], however, acquired linezolid resistance genes (cfr, optrA and/or poxtA) are being increasingly reported in different enterococcal species and across different settings [2][3][4][5][6][7]. Among the three transferable linezolid resistance genes, optrA has been the main one responsible for the recent increase in linezolid-resistant enterococci (LRE) in human isolates [8][9][10][11][12][13]. According to available studies, optrA-carrying LRE are globally circulating in hospitals since at least 2005 [14], while the first description in food-producing animals dates from 2008 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin and related compounds are credited with a wide spectrum of biological activities. [1] Numerous studies have shown that curcumin possess antiinflammatory, [2] antioxidant, [3] antitumor, [4] antimalarial, [5] and analogues included Ph, m-MeO-C 6 H 4 , 3,4-di-MeO-C 6 H 3 , 3,4,5-tri-MeO-C 6 H 2 , p-Br-C 6 H 4 , p-F-C 6 H 4 , p-CF 3 many other biological activities. [6] Despite its broad spectrum of activities and good safety profile curcumin is hard to develop as a drug because of its poor oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…While this mechanism of linezolid resistance in E. faecium and S. au-reus is predominant in Korea, resistance due to variants in ribosomal proteins L3, L4, and L22 have also been reported [3]. Acquisition of the linezolid resistance gene cfr or, more recently, optrA is more threatening because these genes are plasmid encoded and, thus, transmissible [4]. Human isolates of optrApositive linezolid-nonsusceptible Enterococcus faecalis (LNSEF) were reported first in 2016 in China [4] and later in the USA, Sweden, France, Thailand, Taiwan, Malaysia, and Korea [3,5].…”
mentioning
confidence: 99%